A nomogram for predicting prognostic value of inflammatory response biomarkers in decompensated cirrhotic patients without acute‐on‐chronic liver failure. Issue 11 (26th March 2017) - Cai, Y.‐J.; Dong, J.‐J.; Dong, J.‐Z.; Chen, Y.; Lin, Z.; Song, M.; Wang, Y.‐Q.; Chen, Y.‐P.; Shi, K.‐Q.; Zhou, M.‐T.
Summary: Background: Inflammation plays a vital role in liver cirrhosis progression and prognosis. Aim: To investigate the prognostic significance of inflammatory response markers in decompensated cirrhotic patients without acute‐on‐chronic liver failure (ACLF). Methods: Independent predictors were identified using multivariate Cox model and then assembled into a nomogram to predict survival. Concordance index (C‐index) and time‐dependent receiver operating characteristics (td‐ROC) analysis were adopted to evaluate and compare the performance of nomogram, model for end‐stage liver disease (MELD) scores, MELD‐Na and Chronic Liver Failure‐consortium score for acute decompensated (CLIF‐C ADs). Results: A total of 902 decompensated cirrhotic patients with different aetiologies were enrolled, with 6‐month, 1‐year and 3‐year mortality of 18.6%, 24.4% and 34.8%, respectively. The cut‐off values for neutrophil‐to‐lymphocyte ratio (NLR) and lymphocyte‐to‐monocyte ratio (LMR) determined by X‐tile program were 5.7 and 1.1 respectively. Patients with NLR>5.7 or LMR≤1.1 had significantly higher mortality ( P < 0.001). Independent factors derived from multivariable Cox analysis of development cohort to predict mortality were age, NLR and LMR (hazard ratio (HR): 1.064, 95% confidence interval (CI): 1.045–1.084, P < 0.001; HR: 1.124, 95%CI: 1.091–1.158, P < 0.001; HR: 0.794, 95%CI: 0.702–0.898, P < 0.001, respectively). The C‐indexes of nomogram were higher than that of MELD score, MELD‐Na and CLIF‐C ADs for predicting survival. The tdROC and decision curves showed that nomogram was superior to MELD score, MELD‐Na and CLIF‐C ADs. Similar results were observed in validation cohort. Conclusion: The proposed nomogram with neutrophil‐to‐lymphocyte ratio and lymphocyte‐to‐monocyte ratio resulted in accurate prognostic prediction for decompensated cirrhotic patients without ACLF. Abstract : Linked Content This article is linked to Forest and Cai and Shi et al papers. To view these articles visithttps://doi.org/10.1111/apt.14183 andhttps://doi.org/10.1111/apt.14208 .